Phenotypic and molecular characterization of blaCTX-M-3 and blaCTX-M-55-producing monophasic Salmonella enterica serovar Typhimurium in Greece. (September 2022) - Protonotariou, Efthymia; Meletis, Georgios; Papadopoulos, Theofilos; Kagkalou, Georgia; Tychala, Areti; Chattaway, Marie Anne; Mandilara, Georgia; Nair, Satheesh; Skoura, Lemonia
Highlights: In recent years monophasic Salmonella Typhimurium has become an emerging serovar causing foodborne disease worldwide We analyzed three multi-drug resistant Salmonella spp recovered from pediatric patients using WGS and conventional methods WGS, serotyping and PCR analysis revealed that all isolates were identified as monophasic S. Typhimurium, ST 34, eBG 1 WGS revealed ESBL production in all three strains; the presence of plasmid-mediated blaCTX-M-3 in two strains and the chromosomally encoded blaCTX-M-55 plus qnrS1 in the third strain ABSTRACT: Objectives: To characterize three Salmonella enterica serovar Typhimurium strains using whole genome sequencing (WGS) and conventional methods. The isolates were recovered from three pediatric patients in Greece as part of the hospital's epidemiological surveillance system during 2016 to 2018. Methods: Bacterial identification and antimicrobial susceptibility testing was performed using the VITEK 2 automated system, disc diffusion test, and MIC gradient test while serotyping by the slide agglutination method. Detection of resistance genes, eBurst groups (eBG), assignment to sequence types, single nucleotide polymorphism (SNP) typing, location and characterization of drug resistance regions, and in silico plasmid detection were carried out using WGS. Results: All strains were identified as S . Typhimurium-monophasic, ST34, eBG1 with antigenic formula 1, 4, [5], 12:i:-. They were phenotypically resistant to most antibiotics tested except piperacillin/tazobactam, imipenem, and co-trimoxazole. WGS revealed the chromosomally located genes encoding the ASSuT (ampicillin, streptomycin, sulfonamides, and tetracycline) resistant pattern in all three strains. WGS revealed extended spectrum ß-lactamase (ESBL) production in all three strains, the presence of blaCTX-M-3 on an IncI1 plasmid in two strains isolated in 2018, and the chromosomally encoded blaCTX-M-55 plus qnrS1 (resistance to ciprofloxacin) in the strain isolated in 2016. The two strains from 2018 were isolated from the same hospital ward and were genetically related. Conclusions: The emergence of ESBL among S . 1, 4, [5], 12:i:- is worrisome due to its increasing antimicrobial resistance phenotype, making clinical treatment difficult. WGS provides an alternative to traditional methods of identification and genomic characterisation of strains, and serves to better understand their epidemiological dynamics and bacterial pathogenesis.